2004
DOI: 10.1080/01902140490517809
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Induce Activation of Human Lung Fibroblasts in Vitro

Abstract: Mast cells are able to induce proliferation of skin fibroblasts; however, their effect on lung fibroblasts has not been clearly established. Using in vitro cocultures of rat or human mast cells with lung fibroblasts, the authors determined whether mast cells alter proliferation, collagen synthesis, and metalloproteinase production from lung fibroblasts. Mast cells enhanced the proliferation of human fibroblasts (mean +/- SEM: 90% +/- 4.7% increase, P < .001) while inhibiting fibroblast collagen synthesis (48.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 39 publications
2
26
0
1
Order By: Relevance
“…As compared to the control (fibroblasts alone) and no cell contact (NC) groups, the proliferation of pulmonary fibroblasts was significantly increased in our co-culture with contact (CC) group. These results are in agreement with previous studies in which MCs promoted fibroblast proliferation in vitro (Garbuzenko et al 2004, Foley et al 2011). In addition, our co-culture conditions promoted fibroblast differentiation into myelofibroblasts (increased α-SMA expression), and induced increased production of growth factors (bFGF, TGFβ1) and Type I collagen.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As compared to the control (fibroblasts alone) and no cell contact (NC) groups, the proliferation of pulmonary fibroblasts was significantly increased in our co-culture with contact (CC) group. These results are in agreement with previous studies in which MCs promoted fibroblast proliferation in vitro (Garbuzenko et al 2004, Foley et al 2011). In addition, our co-culture conditions promoted fibroblast differentiation into myelofibroblasts (increased α-SMA expression), and induced increased production of growth factors (bFGF, TGFβ1) and Type I collagen.…”
Section: Discussionsupporting
confidence: 83%
“…These foci are primarily comprised of pulmonary fibroblasts and myofibroblasts, which differentiate from fibroblasts in the pulmonary interstitium. Both fibroblasts and myofibroblasts predominantly secrete Types I and III collagen, the major components of the ECM.Previous studies of pulmonary fibrosis have emphasized that mast cells (MCs) promoted the formation of tissue fibrosis via their interactions with pulmonary fibroblasts (Garbuzenko et al 2004). In rats with pulmonary fibrosis, investigators have found that MCs aggregate in areas of pulmonary fibroblast hyperplasia.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Interactions between these two cell types are known to have proinflammatory effects (15)(16)(17), but less is known about mediators involved in tissue remodeling. Matrix metalloproteinases (MMP) are zinc and calcium-dependent proteases that digest most ECM components.…”
mentioning
confidence: 99%
“…Mast cells also modulate functional activity of fibroblasts. These cells activate skin [1] and pulmonary [2] fibroblasts. During the development of autoprosthesis, the number of mast cell varied insignificantly from 4.37±0.33 to 3.94±0.25 per 0.01 mm 2 unit area.…”
Section: Resultsmentioning
confidence: 98%